Audiometric thresholds and auditory processing in children with early malnutrition: a retrospective cohort study - Zuanetti, Patricia Aparecida; Laus, Maria Fernanda; Anastasio, Adriana Ribeiro Tavares; Almeida, Sebastião de Sousa; Fukuda, Marisa Tomoe Hebihara (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Malnutrition is one of the causes of changes in cell metabolism. The inner ear has few energy reserves and high metabolism. The aim of this study was to analyze whether malnutrition at an early age is related to impairment of auditory processing abilities and hearing abnormalities. DESIGN AND SETTING: Retrospective cohort study conducted in a tertiary public hospital. METHODS: 45 children participated, divided as follows: G1, children diagnosed with malnutrition in their first two years of life; G2, children without history of malnutrition but with learning difficulties; G3, children without history of malnutrition and without learning difficulties. Tympanometry, pure-tone audiometry and the Staggered Spondaic Word (SSW) test (auditory processing) were performed. Statistical inferences were made using the Kruskal-Wallis test (α = 5%) and the test of equality of proportions between two samples (α = 1.7%). RESULTS: None of the 45 children participating in this study presented hearing deficiencies. However, at six of the eight frequencies analyzed, the children in G1 presented hearing thresholds lower than those of the other groups. In the auditory processing evaluation test, it was observed that 100% of the children in G1 presented abnormal auditory processing and that G1 and G2 had similar proportions of abnormalities (P-values: G1/G2 = 0.1; G1/G3 > 0.001; G2/G3 = 0.008). CONCLUSIONS: Malnutrition at an early age caused lowering of the hearing levels, although this impairment could not be considered to be a hearing deficiency. Every child in this group presented abnormalities in auditory processing abilities.